Peran BIPA dalam internasionalisasi perguruan tinggi Islam: adaptasi akademik di Indonesia - Asri Nuranisa Dewi (Curricula: Journal of Curriculum Development, 2026)
The Indonesian Language for Foreign Speakers (BIPA) program plays an important role in the internationalization of higher education in Indonesia, including Islamic universities. However, research on its support for international students’ academic adaptation remains limited. This study aims to investigate the role of BIPA in the internationalization of Islamic universities, focusing on international student admission practices and academic adaptation through a literature review approach. Data were collected from national and international journal articles, academic books, and relevant policy documents related to BIPA, higher education internationalization, and international students’ academic adjustment. The data were analyzed using thematic analysis to identify patterns, research trends, and gaps. The findings reveal three dominant research patterns: studies on BIPA management, curriculum development, and the integration of Islamic values and the cultural adaptation of international students. Nevertheless, the role of BIPA in developing students’ academic language readiness remains underexplored. This study argues for repositioning BIPA as an academic acculturation program that not only facilitates social and cultural adjustment but also strengthens academic language competence, thereby supporting the academic success of international students in Islamic higher education institutions.